Factores que determinan las deficiencias del sistema de información contable financiera de las empresas privadas en el departamento del Quindío correspondientes al sector hotelero urbano (2011)
This work is part of the research line "The financial function" which explains the shortcomings in the accounting and financial systems for the urban hotel sector of the Department of Quindío in order to form a documentary basis for the update of the accounting features of this economic sector as well as enabling its query as a reference point for future research.